Millennial Generation Students Search the Web Erratically, with Minimal Evaluation of Information Quality. A Review of: Taylor, A. (2012). A study of the information search behaviour of the millennial generation. Information Research, 17(1), paper 508. Retrieved from http://informationr.net/ir/17-1/paper508.html - Dominique Daniel (Evidence Based Library and Information Practice, 2013)
Objective – To identify how millennial generation students proceed through the information search process and select resources on the web; to determine whether students evaluate the quality of web resources and how they use general information websites. Design – Longitudinal study. Setting – University in the United States. Subjects – 80 undergraduate students of the millennial generation enrolled in a business course. Methods – The students were required to complete a research report with a bibliography in five weeks. They also had to turn in interim assignments during that period (including an abstract, an outline, and rough draft). Their search behaviour was monitored using a modified Yahoo search engine that allowed subjects to search, and then to fill out surveys integrated directly below their search results. The students were asked to indicate the relevance of the resources they found on the open web, to identify the criteria they used toevaluate relevance, and to specify the stage they were at in the search process. They could choose from five stages defined by the author, based on Wilson (1999): initiation, exploration, differentiation, extracting, and verifying. Datawere collected using anonymous user IDs and included URLs for sources selected along with subject answers until completion of all assignments. The students provided 758 distinct web page evaluations. Main Results – Students did not progress in orderly fashion through the search process, but rather proceeded erratically. A substantial number reported being in fewer than four of the five search stages. Only a small percentage ever declared being in the final stage of verifying previously gathered information, and during preparation of the final report a majority still declared being in the extracting stage. In fact, participants selected documents (extracting stage) throughout the process. In addition, students were not much concerned with the quality, validity, or authority of their sources, reporting that the main criteria they used to evaluate a web resource were its understandability, the amount of information in the source, its accuracy, and its recency. During the last stage of the assignment the main criteria were understandability and the amount of information. Finally, students used general information websites like Wikipedia throughout the process, but especially while preparing the final report. Conclusion – The search behaviour of millennial students does not conform to existing search models. The models are appropriate but the execution of these models by students is problematic. Students gathered documents, including general websites like Wikipedia, through all stages of the assignment, including the preparation of the final report. They are likely to procrastinate and do some backfilling. Furthermore they show little concern for the validity of sources: very few verified their sources and quality of the information gathered was not a priority for them. Those findings point to a problem of perception rather than a lack of information search skills: millennial students know how to search and filter, but they do not believe that there is an objective standard to evaluate information and they have a non-critical view of information. More research about the causes of such perception should help us identify effective strategies to help students improve their searches.